2017
DOI: 10.1007/s11669-017-0546-7
|View full text |Cite
|
Sign up to set email alerts
|

Critical Systematic Evaluation and Thermodynamic Optimization of the Fe-RE System: RE = Gd, Tb, Dy, Ho, Er, Tm, Lu, and Y

Abstract: As the second part of the thermodynamic study of binary Fe-RE system, critical evaluations and optimizations of all available phase diagrams and thermodynamic data for the Fe-heavy RE (heavy RE = Gd, Tb, Dy, Ho, Er, Tm, Lu, and Y) systems were conducted to obtain reliable thermodynamic functions of all the phases in the systems. In the thermodynamic modeling of the heavy RE systems, systematic variations in the phase diagrams and thermodynamic properties such as the enthalpy of mixing in the liquid state and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 103 publications
0
4
0
1
Order By: Relevance
“…The first CALPHAD assessment of the Y-Fe system was reported by Du et al [121] and later refined by Lü et al [122] to better replicate the ternary phase equilibria in the Y-Fe-Ni system. However, as mentioned by Konar et al [123], the Gibbs energy of compounds reported in [121] was distinct from the experimental data, and neither the thermodynamic parameters for liquid or solid phases nor the invariant reactions were given in the updated assessment [122], making it impossible to evaluate. The Y-Fe system was re-assessed by Kardellass et al [124,125] considering homogeneity range in the Y 6 Fe 23 and the YFe 2 phases compared to the stoichiometric compounds previously considered.…”
Section: Thermodynamics Properties Of the Y(co-fe-ni) 5 Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The first CALPHAD assessment of the Y-Fe system was reported by Du et al [121] and later refined by Lü et al [122] to better replicate the ternary phase equilibria in the Y-Fe-Ni system. However, as mentioned by Konar et al [123], the Gibbs energy of compounds reported in [121] was distinct from the experimental data, and neither the thermodynamic parameters for liquid or solid phases nor the invariant reactions were given in the updated assessment [122], making it impossible to evaluate. The Y-Fe system was re-assessed by Kardellass et al [124,125] considering homogeneity range in the Y 6 Fe 23 and the YFe 2 phases compared to the stoichiometric compounds previously considered.…”
Section: Thermodynamics Properties Of the Y(co-fe-ni) 5 Alloysmentioning
confidence: 99%
“…The Y-Fe system was re-assessed by Kardellass et al [124,125] considering homogeneity range in the Y 6 Fe 23 and the YFe 2 phases compared to the stoichiometric compounds previously considered. Then, Konar et al [123] published a new thermodynamic assessment of the Y-Fe system. However, the use of the modified quasichemical model for the liquid phase renders this work incompatible with the substitutional model used in other assessments.…”
Section: Thermodynamics Properties Of the Y(co-fe-ni) 5 Alloysmentioning
confidence: 99%
“…Thus, we conclude that phase segregation takes place in RE‐TM films, [ 89,90,93–96 ] but atoms of different species tend to interdiffuse upon aging because the mixing enthalpy of TM and RE atoms is negative. [ 76,97,98 ]…”
Section: Magnetic Properties Of Rare‐earth Transition‐metal Ferrimagnetsmentioning
confidence: 99%
“…Thus, we conclude that phase segregation takes place in RE-TM films, [89,90,[93][94][95][96] but atoms of different species tend to interdiffuse upon aging because the mixing enthalpy of TM and RE atoms is negative. [76,97,98] This chemical and structural disorder leads to a distribution of the magnitude of magnetic moments, exchange interactions, and local electrostatic fields. Although such a randomization does not prevent the formation of a collective magnetic order, it causes important deviations from the ideal picture of collinear ferro-and ferrimagnets.…”
Section: Atomic Structure and Magnetic Disordermentioning
confidence: 99%
“…К указанному семейству интерметаллидов, как правило, относят соединение YFe 2 , где атом иттрия с незаполненной f -оболочкой является изоэлектронным аналогом трехвалентного редкоземельного атома. Интерметаллиды YFe 2 и TbFe 2 характеризуются высокими T C (соответственно 535 и 700 K [7]), значительными магнитострикционными [8], магнетокалорическими [9] и магнитооптическими [10][11] эффектами, а также большой способностью к абсорбции водорода [12]. При легировании данных соединений атомами других переходных металлов, их магнитные свойства существенно трансформируются вследствие изменения параметров кристаллической решетки и обменных взаимодействий [13,14].…”
Section: Introductionunclassified